Le design graphique et la traduction au prisme de la transcréation - Gabriele Čepulytė (Appareil)
The hypothesis developed in this article is that of a reversal of the hierarchical relationship between form and content in graphic design, through the concept of transcreation of the Brazilian poet and translator Haroldo de Campos. Starting from the assumption that translation and graphic design, as formal practices, share the same relationship of subordination to content by the fact that they manipulate textual messages, the author relates the “verbivocovisual” practices of Brazilian concrete poetry with the shift towards semantic unification operated by the designer Karl Gerstner. Posing complex problems of translation in the entanglement of the message and its form, poetry is then the very example of the untranslatable, justifying the practice of transcreation of Haroldo de Campos. He derives a translation from it as a re-project of the aim of a text, through the re-interplay of the textual engendering device in the target language. The transposition of the concept of transcreation to graphic design then takes place at the level of its own creative process, including variation as an open possibility of application to diverse objects. Through Max Bense’s theory of aesthetic information, underlying poetic transcreation, graphic design is defined by the continuous creation of possibilities emancipating itself from the semantic content, which has become inessential through its repetition within a system of varying forms. Graphic design then develops through the necessary association with a field, which turns out to be a media environment : this highlighting opens the subject towards a questioning of what a media-driven transcreation could be.